AVT-VQDB-UHD-1-Appeal: A UHD-1/4K Open Dataset for Video Quality and Appeal Assessment Using Modern Video Codecs - Rao, Rakesh Rao Ramachandra; Goring, Steve; Elmeligy, Bassem; Raake, Alexander (IEEE International Workshop on Multimedia Signal Processing, 2023)
A number of factors play an important role in the perception of video quality for streaming and other services, key among them being encoding-related degradations. Hence, newer codecs are developed with the goal of optimizing video quality for a given encoding setting. Here, subjective studies are an efficient method to evaluate the performance of such newer codecs. Furthermore, contextual factors impact the perception of video quality, e.g., the appeal of the content itself. To this end, this paper presents a subjective study targeting both quality and appeal assessment of videos. For this purpose, a subjective study consisting of three different parts is conducted. Firstly, participants were asked to rate the appeal of the uncompressed UHD-1/4K source content with a duration of 8 - 10s each. Following this, the video quality of these source videos individually encoded with either the HEVC/H.265, AV1, or VVC/H.266 video codec was rated. A wide range of encoding conditions in terms of resolution (360p to 2160p) and bitrate (100kbps to 15mbps) is used to encode the videos, so as to enable the applicability of the data to real-world settings. In the last part, subjects are again asked to rate the appeal of the uncompressed source content. The results are analyzed to assess the impact of different encoding conditions on perceived video quality. In addition, the impact of appeal on video quality and vice-versa is also investigated. Furthermore, an objective quality assessment with different state-of-the-art full-reference, bitstream-based, and hybrid models including the newer codecs AV1 and VVC is presented. The subjective dataset including test design, subjective results, sources, and encoded audiovisual contents are made publicly available following an open science approach.